DEVELOPMENT OF READING BOOK FOR CLASS VII STUDENTS USING THE STRATEGY TPS ((THINK, PAIR, SHARE) LEARNING MODEL TO IMPROVE STUDENTS’ READING SKILLS AT SMP YAPIS MERAUKE - Marnina Marnina; Margaretha F Narahawarin (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
English as a foreign language has been include in the education curriculum in Indonesia since Indonesia achieved independence studying English is not only an effort by the government to improve the quality of Indonesian human resources especially students’ knowledge but also as a capital for students to face future challenges that require students to be active in English both spoken and written. The purpose of this study was to design and develop reading books for class VII students of SMP Yapis Merauke using learning model the TPS (Think, Pair, Share) strategy to improve students’ reading skills and increase students’ interest in reading so that students do not feel bored in learning to read and can improve students learning outcomes. This research was conducted at SMP Yapis Merauke. The subjects were students of class VII SMP Yapis Merauke. This type of research is research and development or Research and Development (R & D) Borg and Gall (1983:772) state that educational research and development is a process used to develop and validate educational products. There are 2 types of instruments used, namely the first to collect information for needs analysis and the second to evaluate the product. While the research procedures are: (1) conducting a needs analysis which is an initial observation, review of literature and analyzing data, (2) writing material, namely the process of writing material based on topics, grammar based on an analysis of students needs; (3) Expect Assessment, namely the draft is evaluated in the form of a questionnaire about the material; (4) revise the draft namely the material is revised based on feedback and suggestions from experts; (5) writing the final draft of the material which is used as additional material to improve students’ mastery and reading skills. The expected results of this study are increasing students’ skills in reading and the availability of reading books as supporting facilities in learning English both in the classroom and at the students’ home. The output of this study was in the form of reading books for class VII students of SMP Yapis Merauke using the TPS (Think, Pair, Share) strategy learning model